Making laws that work : why laws fail and how we can do better - Goddard, David (London [England] : Hart Publishing, 2022)
"This book examines why laws fail and provides strategies for making laws that work. Why do some laws fail? And how can we make laws that actually work? This helpful guide, written by a leading jurist, provides answers to these questions and gives practical strategies for law-making. It looks at a range of laws which have failed; the 'damp squibs' that achieve little or nothing in practice; laws that overshoot their policy goals; laws that produce nasty surprises; and laws that backfire, undermining the very goals they were intended to advance. It goes on to examine some of the reasons why such failures occur, drawing on insights from psychology and economics, including the work of Kahneman and others on how humans develop narratives about the ways in which the world works and make predictions about the future. It provides strategies to reduce the risk of failure of legislative projects, including adopting a more structured and systematic approach to analysing the likely effects of the legislation; ensuring we identify the limits of our knowledge and the uncertainties of our predictions; and framing laws in a way that enables us to adjust the way they operate as new information becomes available or circumstances change. Key themes include the importance of the institutions that administer the legislation, of default outcomes, and of the 'stickiness' of those defaults. The book concludes with helpful checklists of questions to ask and issues to consider, which will be of benefit to anyone involved in designing legislation."--
Introduction Part I - Setting the Scene -- 1. When Legislation Fails -- 2. The Ways in Which Legislation Fails -- 3. Learning from Past Failures -- 4. How Humans (Including Legal Designers!) Actually Make Decisions Part II - Lessons for Legal Designers -- 5. Adopting a Structured Approach to Designing New Laws -- 6. What Is the Current Position? -- 7. What Is the Legislation Aiming to Change? -- 8. Who Are the Audiences for the Legislation? -- 9. What Institutions Will the Legislation Depend on? Do They Have the Capacity to Play Their Role? -- 10. How Will the Legislation Change Behaviour? How Might That Go Wrong? -- 11. Adaptive Legislation -- 12. The Implications of New and Emerging Technologies -- 13. Cross-Border Issues -- 14. Attempting Default Settings -- 15. Reducing Complexity Part III -- 16. Checklist for Law Making -- 17. The Primary Checklist -- 18. Benefits Checklist -- 19. Compliance Checklist -- 20. Institutions Checklist -- Appendix 1 Legislation Checklist -- Appendix 2 Background Reading for Legal Designers
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Bill drafting; Legislation; Electronic books